Efektifitas Konseling Kelompok Dengan Teknik Behavioral Contract Untuk Mengurangi Kebiasaan Membolos Siswa Kelas Xi Sma Negeri 8 Kota Bengkulu - aroyan mutaqin; DODO SUTARDI; HENI SULUSYAWATI (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2018)
This study aims to: (1) to find out the habit of ditching class XI students of Bengkulu City Senior High School 8 before being given group counseling services with behavioral contract techniques, (2) to find out the habit of ditching class XI students of Bengkulu 8 High School after being given group counseling services with behavioral contract techniques, and (3) to determine the effectiveness of group counseling services with behavioral contract techniques in reducing the habit of ditching class XI students of SMA Negeri 8 Kota Bengkulu. The method used is action research in guidance and counseling services. This study involved six students who indicated truant habits, namely (AH, ART, FBF, F, and RSF) from class XI of SMA Negeri 8 Kota Bengkulu, obtained from the results of documentation in the form of the last attendance in August. After the counselee's identification, group counseling services are conducted with a behavioral contract technique. The procedure for classroom action research is carried out in 4 stages, namely 1) planning, 2) implementation, 3) observation, 4) reflection. The results showed that: (1) The results of the analysis before being given group counseling services with behavioral contract techniques, the habit of ditching students on average there are five times in one month, (2) Results of analysis after being given group counseling services with behavioral contract techniques, student habits ditching experienced a decrease in the previous one in five months twice a month. (3) The results of the analysis can be concluded that the implementation of group counseling services with highly effective behavioral contract techniques is used to reduce the habit of skipping school in class XI Bengkulu 8 High School students that implementing group counseling services with highly effective behavioral contract techniques is used to reduce truant habits school for class XI students of SMA Negeri 8 Kota Bengkulu.